Determination of flow characteristics in the vegetated compound channels - Ismail, Zulhilmi; Harun, Sobri; Ibrahim, Zulkiflee (Faculty of Civil Engineering, 2009)
Floods are frequent events occur in the Asia, Europe and many parts of the world. The recent floods in Malaysia such as in the states of Johor, Pahang, Kelantan, Terengganu and Kedah resulted huge damages to buildings, infrastructures, crops and also human suffering. In overbank flow conditions, a large momentum exchange takes place between main channel and floodplain flows. An experimental study on the effects of submerged vegetation on floodplain and oneline emergent vegetation along the edge of floodplain on the river hydraulics during flooding is carried out in the laboratory. It is important to understand the hydraulic processes in order to maintain the rivers as safe and environmental-friendly. The results on stage-discharge relationship, longitudinal velocity profiles and roughness parameter for inbank and overbank flows in a straight compound channel are presented in this report. It is found that the vegetation influences stage-discharge where retardation of flow takes place. The high velocity zone is observed to be in main channel and less fluid momentum transfer takes place with the presence of vegetation. Also, channel roughness increases for vegetated floodplain.